A model of software component interactions using the call graph technique - Nooraini, Ismail (2013)
Interaction information that is related to operations between components is important, especially when the program needs to be modified and maintained. Therefore, the affected components must be identified and matched based on the requirement of the system. This information can be obtained through performing the code review technique, which requires an analyst to search for specific information from the source code, which is a very time consuming process. This research proposed a model for representing software component interactions where this information was automatically extracted from the source code in order to provide an effective display for the software components interaction representation. The objective was achieved through applying a research design methodology, which consists of five phases: awareness of the problem, suggestion, development, evaluation, and conclusion. The development phase was conducted by automatically extracting the components‘ interaction information using appropriate reverse engineering tools and supporting programs that were developed in this research. These tools were used to extract software information, extract the information of component interactions in software programs, and transform this information into the proposed model, which was in the form of a call graph. The produced model was evaluated using a visualization tool and by expert review. The visualization tool was used to display the call graph from a text format into a graphical view. The processed model evaluation was conducted through an expert review technique. The findings from the model evaluation show that the produced model can be used and manipulated to visualize the component interactions. It provides a process that allows a visualization display for analysts to view the interaction of software components in order to comprehend the components integrations that are involved. This information can be manipulated and improved the program comprehension, especially for other software maintenance purposes.